Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding

Fluorescence quenching and time-resolved fluorescence studies of alpha-Mannosidase from Aspergillus fischeri (NCIM 508) - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2007)
Apart from the vital role in glycoprotein biosynthesis and degradation, alpha-mannosidase is currently an important therapeutic target for the development of anticancer agents. Fluorescence quenching and time-resolved fluorescence of alpha-mannosidase, a multitryptophan protein from Aspergillus fischeri were carried out to investigate the tryptophan environment. The tryptophans were found to be differentially exposed to the solvent and were not fully accessible to the neutral quencher indicating heterogeneity in the environment. Quenching of the fluorescence by acrylamide was collisional. Surface tryptophans were found to have predominantly positively charged amino acids around them and differentially accessible to the ionic quenchers. Denaturation led to more exposure of tryptophans to the solvent and consequently in the significant increase in quenching with all the quenchers. The native enzyme showed two different lifetimes, tau (1) (1.51 ns) and tau (2) (5.99 ns). The average lifetime of the native protein (tau) (3.187 ns) was not affected much after denaturation (tau) (3.219 ns), while average lifetime of the quenched protein samples was drastically reduced (1.995 ns for acrylamide and 1.537 ns for iodide). This is an attempt towards the conformational studies of alpha-mannosidase.
Keywords: alpha-Mannosidase; Denaturation; fluorescence; lifetime; Solute quenching

Comparative studies of two araceous lectins by steady state and time-resolved fluorescence and CD spectroscopy - Dharker, Poorva N.; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Khan, Mohammad Islam; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2009)
Transitions in the tryptophan microenvironment and secondary structure of two monocot lectins from Sauromatum guttatum and Arisaema tortuosum under different denaturing conditions were studied by steady state and time resolved fluorescence and CD spectroscopy. The lectins exist as tetramers with a single tryptophan residue estimated per monomer, present in a polar environment. Quenching with ionic quenchers showed predominantly electropositive environment for tryptophan residues. Acrylamide had maximum quenching effect. A decrease in KI quenching due to lectin denaturation indicated redistribution of charges as a result of possible conformational change. The two values for lifetimes of tryptophanyl population (1.2-1.4 and 6.3-6.4 ns) reduced substantially on quenching or denaturation. Similarly, both the lectins showed a drastic loss of secondary structure in 5 M Gdn-HCl or 6 M Urea or at pH 2.0 and below. For the first time araceous lectins, like legume lectins are shown to bind adenine. The presence of a compact structure at alkaline pH 10.0-12.0 was observed in CD spectra.
Keywords: Araceae lectins; Denaturation; fluorescence; Lifetime spectroscopy; Secondary structure

Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin

Comparison of polymer induced and solvent induced trypsin denaturation: the role of hydrophobicity - Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2014)
Trypsin adsorption from aqueous buffer by various copolymers of allyl glycidyl ether-ethylene glycol dimethacrylate (AGE-EGDM) copolymer with varying crosslink density increases with increasing crosslink density and the effect slowly wears off after reaching a plateau at 50% crosslink density. The copolymer with 25% crosslink density was reacted with different amines with alkyl/aryl side chains to obtain a series of copolymers with 1,2-amino alcohol functional groups and varying hydrophobicity. Trypsin binding capacity again increases with hydrophobicity of the reacting amine and a good correlation between logP(octanol) of the amine and protein binding is observed. The bound trypsin is denatured to the extent of 90% in spite of the presence of hydrophilic hydroxyl and amino groups. The behavior was comparable to that in mixtures of aqueous buffer and water-miscible organic co-solvents where the solvent concentration required to deactivate 50% of the enzyme (C-50) is dependent on logP(octanol) of the co-solvent. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Denaturation; Hydrophobicity; Polymer; Trypsin